(NsTILISTIKA SOWREMENNOGO FRANCUZSKOGO QZYKA (B:s (Nu^EB(B. (NDLQ IN(B-(NTOW I FAK(B. (NINOSTR(B. (NQZ(B. /s - (NmOREN(B, (NmARIQ kARLOWNAs; (NtETEREWNIKOWA(B, (NnADEVDA nIKOLAEWNAs ((NmOSKWA (B:s (NiZD(B-(NWO LIT(B. (NNA INOSTR(B. (NQZ(B.,s, 1960)
(NbIBLIOGR(B.: (NS(B. 284-296s
Keywords: (NfRANCUZSKIJ QZYK (B- (NsTILISTIKAs